2008
DOI: 10.1152/ajpheart.00074.2008
|View full text |Cite
|
Sign up to set email alerts
|

Darbepoetin-α prevents progressive left ventricular dysfunction and remodeling in nonanemic dogs with heart failure

Abstract: Rastogi S, Imai M, Sharov VG, Mishra S, Sabbah HN. Darbepoetin-␣ prevents progressive left ventricular dysfunction and remodeling in nonanemic dogs with heart failure. Am J Physiol Heart Circ Physiol 295: H2475-H2482, 2008. First published October 24, 2008 doi:10.1152/ajpheart.00074.2008.-In anemic patients with heart failure (HF), erythropoietin-type drugs can elicit clinical improvement. This study examined the effects of chronic monotherapy with darbepoetin-␣ (DARB) on left ventricular (LV) function and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
2
13
0
1
Order By: Relevance
“…Caspase-3 activity increased in MA-ISO and was not altered in YA-ISO, supporting the idea that nonsenescent animals are more vulnerable to injury and stress than their younger counterparts. This finding is consistent with a previous study showing that caspase-3 overexpression depresses cardiac function in mice, and with a report that caspase-3 expression is elevated in a dog model of HF (14,45). An in vitro study demonstrated that caspase-3 activation leads to a reduction of contractile reserve in LV cardiomyocytes (30).…”
Section: R496 Age Exacerbates Impairments In Contractile Reservesupporting
confidence: 93%
See 1 more Smart Citation
“…Caspase-3 activity increased in MA-ISO and was not altered in YA-ISO, supporting the idea that nonsenescent animals are more vulnerable to injury and stress than their younger counterparts. This finding is consistent with a previous study showing that caspase-3 overexpression depresses cardiac function in mice, and with a report that caspase-3 expression is elevated in a dog model of HF (14,45). An in vitro study demonstrated that caspase-3 activation leads to a reduction of contractile reserve in LV cardiomyocytes (30).…”
Section: R496 Age Exacerbates Impairments In Contractile Reservesupporting
confidence: 93%
“…Additionally, pharmacological inhibition of caspase-3 improved postischemic contractile recovery in the isolated rat heart (49). The present in vivo results, along with data from several models of cardiovascular injury, support the notion that caspase activation plays a major role in the development of contractile dysfunction (9,30,45,49). The precise mechanisms of caspase-3-induced reductions in systolic performance are uncertain but may involve perturbations in Ca 2ϩ homeostasis or direct effects on the contractile proteins of the sarcomere (9,47,49).…”
Section: R496 Age Exacerbates Impairments In Contractile Reservesupporting
confidence: 70%
“…The usefulness of ESA in CHF has been shown in animal studies where its use in CHF after myocardial infarction or after production of cardiac damage from other causes, with or without improving the Hb, has improved endothelial dysfunction, increased neovascularization of the heart muscle, and reduced apoptosis of cardiomyocytes, oxidative stress, inflammation, fibrosis, and hypoxic damage, and prevented functional impairment of the heart [87,88,89]. At least part of these effects is due to the increase in number and activity of endothelial progenitor cells from the bone marrow [87,88,89].…”
Section: The Non-hematopoietic Biological Effects Of Epomentioning
confidence: 99%
“…At least part of these effects is due to the increase in number and activity of endothelial progenitor cells from the bone marrow [87,88,89]. …”
Section: The Non-hematopoietic Biological Effects Of Epomentioning
confidence: 99%
“…Recombinanthuman EPO administration has been shown to exert a broad tissue-protective effect in a variety of experimental models. In the cardiovascular system, EPO has been shown to exert marked myocardial protective effects against ischemia-reperfusion injury via a reduction of LV infarct size and a significantly decreased apoptotic cell death of cardiomyocytes, which leads to an enhanced recovery of LV function (5,16). Mechanistically, studies have shown that EPO-EPO-R signaling can stimulate the JAK/STAT, MAPK, and phosphatidylinositol 3-kinase/Akt signaling pathways in cardiac cells, much like the signaling in hematopoietic cells (13,14).…”
mentioning
confidence: 99%